Exploring the Efficacy of Economic Openness and FDI Entry in Enhancing Economic Growth in Nigeria - Kutu, Augustine Adebayo (Journal of Posthumanism, 2025)
The aim of this study is to examine the potency of economic openness and FDI entry in enhancing economic growth in Nigeria. Employing the dynamic ARDL method and an annual data spanning from 1986 to 2022, the result shows that economic openness does not in any way plays a key role in promoting economic growth in Nigeria. Although this finding negates our appriori expectation, it strengthen the stand point of the protectionists. According to the protectionists, any government that open up its economy for global integration should be ready to face economic distress. This describes the true picture of the Nigeria economy at the moment. Similarly, the finding revealed that FDI entry is detrimental to growth process in Nigeria, aligning with the dependency theory. According to the dependency theory, FDI entry is a distraction to the economy of the recipient nations. Thus, the study concludes that economic integration is hazardous to the national economy of Nigeria, hence, recommendation is made for the government to embrace import substitution industrialization trade policies to replace imports with the domestic products.